Valorização dos aspectos formais dos artefatos confeccionados por guasqueiros do pampa gaúcho aplicados à joalheria - Alvares, Fabiano da Costa (2015)
By the findings of this research, the gradual diminish of the guasqueiro role (craftsmen who use rowhide as the main raw material), activity which was developed with the formation of the gaucho people. The present work aims to study and highlight the formal aspects of the rawhide, transfering its cultural and esthetic values for the jewelry, using native gemstone from Rio Grande do Sul, promoting the rescue and valorization of this cultural and material patrimony. At the same time it is established a new proposal, the community is motivated to take back values form past, perpetuing its original activity. It is wanted to improve the professional, practical ans theoretical knowledge, contributing to the development of new research.